A microhistory of a mass mobilisation: Peasant agency and solidarity in the 1990 anti-shrimp movement of polder 22, Khulna - Mahtab, Moyukh (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Development Studies, 2020